The Great Lakes Hydrography Dataset: Consistent, Binational Watersheds for the Laurentian Great Lakes Basin1. (20th June 2016) - Forsyth, Danielle K.; Riseng, Catherine M.; Wehrly, Kevin E.; Mason, Lacey A.; Gaiot, John; Hollenhorst, Tom; Johnston, Craig M.; Wyrzykowski, Conrad; Annis, Gust; Castiglione, Chris; Todd, Kent; Robertson, Mike; et al.
Abstract: Ecosystem‐based management of the Laurentian Great Lakes, which spans both the United States and Canada, is hampered by the lack of consistent binational watersheds for the entire Basin. Using comparable data sources and consistent methods, we developed spatially equivalent watershed boundaries for the binational extent of the Basin to create the Great Lakes Hydrography Dataset (GLHD). The GLHD consists of 5, 589 watersheds for the entire Basin, covering a total area of approximately 547, 967 km 2, or about twice the 247, 003 km 2 surface water area of the Great Lakes. The GLHD improves upon existing watershed efforts by delineating watersheds for the entire Basin using consistent methods; enhancing the precision of watershed delineation using recently developed flow direction grids that have been hydrologically enforced and vetted by provincial and federal water resource agencies; and increasing the accuracy of watershed boundaries by enforcing embayments, delineating watersheds on islands, and delineating watersheds for all tributaries draining to connecting channels. In addition, the GLHD is packaged in a publically available geodatabase that includes synthetic stream networks, reach catchments, watershed boundaries, a broad set of attribute data for each tributary, and metadata documenting methodology. The GLHD provides a common set of watersheds and associated hydrography data for the Basin that will enhance binational efforts to protect and restore the Great Lakes.